Single dose single antibiotic versus multiple doses multiple antibiotic prophylaxis in caesarean section, at a tertiary care centre - Pooja P; Veena Hadi; Sahana Rao; Ashalata Mallapur; Geetanjali Katageri (Barpeta Obstetrics and Gynaecological Society, 2021)
Background: Surgical site wound infections and associated complications after caesarean delivery are important causes of maternal morbidity, increased duration of hospital stay and cost of treatment. Prophylactic antibiotic usage decreases the risk of these wound infections. Though single dose preoperative antibiotic prophylaxis is advocated, clinicians are hesitant to adopt this regimen due to differences in patient profile and uncertainty about asepsis. Objectives: To assess whether single dose pre-incision antibiotic prophylaxis is as effective as multiple doses for routine caesarean sections in a tertiary care centre. Materials and methods: This was a quasi-experimental study involving 320 women undergoing caesarean delivery at tertiary care centre. Eligible participants were divided into two groups. Group A received single dose antibiotic prophylaxis of ceftriaxone 1gm intravenously 30-40 minutes before caesarean section and group B received cefotaxime 1g+sulbactam 500mg 30-40 minutes before the caesarean, followed by cefotaxime+sulbactam and ornidazole intravenously for the first 3 post-operative days followed by oral cefixime for the next 5 days. Postoperatively, both groups of patients were followed up for febrile morbidity, infections including urinary, wound, endometritis, and others; and duration of hospital stay. These parameters were compared across the two groups. Results: There were 160 patients in each group. Baseline characteristics, indications for caesarean delivery, operative duration and difficulties were similar. Post-operative morbidities like fever (p=0.5) and wound infection (p=1) did not differ significantly. None of the women needed prolongation of hospital stay. Conclusion: Preoperative single dose antibiotic regimen was as effective as multiple dose multiple antibiotic regimen prophylaxis for routine caesarean delivery. Judicious use of limited antibiotics should be encouraged to decrease antibiotic resistance, with the added benefit of being economical.